2021
DOI: 10.1002/lno.11883
|View full text |Cite
|
Sign up to set email alerts
|

Potential competition between marine heterotrophic prokaryotes and autotrophic picoplankton for nitrogen substrates

Abstract: Heterotrophic prokaryotes have the capacity to uptake inorganic nitrogen (N) substrates. However, it remains unclear what the potential competition is between heterotrophic prokaryotes and autotrophic plankton for N in the ocean, which would shunt the flow of N supporting primary production. To date, it has been difficult to distinguish heterotrophic prokaryotic N uptake from that of autotrophic picoplankton, especially in oligotrophic oceans dominated by cyanobacteria. We carried out field-based DNA stable is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…Second, environmental factors accounted for an additional yet much smaller fraction of variance in relative activities of phycospheric communities. Here, DO, inorganic N, and DIP were the factors with the highest overall impact, which was consistent with findings of many other studies: e.g., oxygen level being a key regulatory factor of aquatic ecosystem processes and the presence of competition between cyanobacteria and phycospheric bacteria for nitrogen and phosphorus sources ( 73 75 ). However, no environmental factors could explain the residuals of relative activities of Microcystis with the rDNA abundances.…”
Section: Discussionsupporting
confidence: 92%
“…Second, environmental factors accounted for an additional yet much smaller fraction of variance in relative activities of phycospheric communities. Here, DO, inorganic N, and DIP were the factors with the highest overall impact, which was consistent with findings of many other studies: e.g., oxygen level being a key regulatory factor of aquatic ecosystem processes and the presence of competition between cyanobacteria and phycospheric bacteria for nitrogen and phosphorus sources ( 73 75 ). However, no environmental factors could explain the residuals of relative activities of Microcystis with the rDNA abundances.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the minimum DO concentration in the water column was higher than 60 μmol L −1 , suggesting that NO x − removal through denitrification was not likely a main cause for the low ratio of NO X − : AOU, although NO X − removal in the oxic water could not be fully excluded. On the other hand, several recent studies report high NH 4 + utilization rates by heterotrophic prokaryotes (Deng et al., 2021; Trottet et al., 2016) and chemolithotrophs (Guerrero‐Feijóo et al., 2018; Pachiadaki et al., 2017; Zhang et al., 2020) in the global dark ocean, suggesting at least part of the NH 4 + was consumed to produce microbial biomass rather being oxidized by nitrifiers. The average NO X − : AOU ratio of 0.16 in our study suggests that 70% (0.16/0.23) of NH 4 + was oxidized and 30% was used for assimilation in the dark ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Heterotrophic bacteria, such as Proteobacteria, have a high affinity for low nutrient concentrations, whereas phytoplankton such as Cyanobacteria are favored by pulses of high nutrient concentrations [ 38 ]. It appears that the addition of glucose in our study promoted heterotrophic bacterial growth, likely because they have higher nutrient-uptake rates than the Cyanobacteria [ 38 , 39 , 40 ] but are dependent on an external carbon source in their competition. Lu et al [ 22 ] showed that, in Harsha Lake, nitrogen and phosphorous decreased rapidly during cyanobacterial growth from June to July.…”
Section: Discussionmentioning
confidence: 90%